2003
DOI: 10.1002/eji.200324462
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of MHC class I molecules on a CD8+ α β T cell clone specifically inhibits non‐antigen‐specific lysis of target cells

Abstract: MHC class I molecules are target molecules recognized by TCR or NK receptors encoded in the NK gene cluster or leukocyte receptor cluster. We show that aggregation of MHC class I molecules by specific monoclonal antibodies on cytotoxic T cells, inhibits the anti-CD94 redirected lysis of P815. This inhibition is not the consequence of apoptosis or anergy of the cytotoxic T lymphocytes. In contrast, aggregation of MHC class I molecules does not inhibit either the anti-CD3 redirected cytotoxicity or the CD94-trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…At this moment, we cannot totally exclude the involvement of open conformers in the inhibitory effect described here since we have not been able to obtain the specific mAbs. Nevertheless, our previous data from primary unstimulated human NK cells (in which the expression of open conformers is probably low) [10], together with the results obtained here with mAb that recognize β2m and those for the anti-HLAB27 mAb inhibition of CD94-redirected lysis of P815 by a CD8 + αβ T cell clone [11]–[12] point to the involvement of classical trimeric human MHC-I molecules. Regarding cis interactions between MHC-I and inhibitory receptors, it has been reported from a murine model, that MHC-I molecules are recognized by Ly49 inhibitory receptors in cis and trans [32].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…At this moment, we cannot totally exclude the involvement of open conformers in the inhibitory effect described here since we have not been able to obtain the specific mAbs. Nevertheless, our previous data from primary unstimulated human NK cells (in which the expression of open conformers is probably low) [10], together with the results obtained here with mAb that recognize β2m and those for the anti-HLAB27 mAb inhibition of CD94-redirected lysis of P815 by a CD8 + αβ T cell clone [11]–[12] point to the involvement of classical trimeric human MHC-I molecules. Regarding cis interactions between MHC-I and inhibitory receptors, it has been reported from a murine model, that MHC-I molecules are recognized by Ly49 inhibitory receptors in cis and trans [32].…”
Section: Discussionmentioning
confidence: 60%
“…In our previous work, we detected that MHC-I crosslinking with anti-mouse IgG F(ab') 2 on NKL cells induced tyrosine phosphorylation [10]. Moreover, the constitutive location of MHC-I proteins within lipid rafts on NKL cells [10], [29], as well as the MHC-I-specific inhibition of CD94-induced MTOC reorientation towards the P815:K14B06 contact area [11]–[12], strongly suggested that the inhibition of non-restricted cytotoxicity by aggregation of MHC class I molecules is mediated by intracellular inhibitory signals triggered by MHC-I. Consistent with these findings, it has recently been described that the constitutive expression of MHC class I molecules on murine macrophages inhibits the TLR4-triggered inflammatory response by association with the src kinase ftp and SHP-2 [13].…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, we can hypothesize that segregation of cross-linked MHC I from lipid rafts could deprive the NK cell synapse of activating signals if some critical transduction molecules were directly or indirectly associated with MHC I proteins. In this regard, it has been described recently that crosslinking MHC I on a CD8 ϩ T cell clone induced a selective inhibition of microtubule organizing center reorientation to-ward anti-CD94-coated beads upon coengagement of CD94 and MHC class I molecules [32].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, anti-MHC I mAb have been described to induce proliferation of peripheral T cells [10,11], activation of nuclear factor-B [29], increases of intracellular Ca 2ϩ , and phosphorylation of p56lck in T cells [11], phospholipase C␥1 [8], p56lck and -associated protein-70 [9], p53/56lyn and p72syk in B cells [30], and Src, paxilin, and focal adhesion kinase in an actin-dependent manner in human endothelial cells [31]. Conversely, inhibition of CD3-mediated activation and more recently, inhibition of CD94-mediated lysis on a cytolytic T cell clone have also been reported [13,32]. Similarly, several authors have described that engagement of MHC I on NK cells results in an inhibitory or stimulating effect on their killing capacity [15,33] or even induction of apoptosis of the fraction of CD56 ϩ cells in peripheral blood mononuclear cells after 8 days of culture in the presence of mAb anti-MHC I by a Fas-independent pathway [12].…”
Section: Discussionmentioning
confidence: 99%
“…The antibody-coated cancer cells were then mixed with CD8 + cytotoxic T cells, leading to CD94-mediated T cell activation and increased CD25 expression. As a result of this interaction, the T cells were prompted to kill the cancer cells (78). This ADCC triggered by CD94 ligation was shown to be independent of TCR stimulation and could be reduced by co-ligation of MHC-I molecules on the T cell.…”
Section: The Effect Of Reverse Mhc-i Signaling On Proliferation Actimentioning
confidence: 99%